Miniature direct-drive two-link using a micro-flat ultrasonic motor. (18th October 2018) - Miyoshi, K.; Mashimo, T.
ABSTRACT: We propose a micro-flat ultrasonic motor that performs a high torque density by a tiny and flat stator for driving a miniature two-link. Such a two-link can be a fundamental technology that enables micro-assembling and micro-manipulation under a microscopic environment. In this paper, we build the micro-flat ultrasonic motor comprising of a flat stator with 2.6 mm in width and height and 1 mm in depth and evaluate the output performance measures. The prototype micromotor shows a torque of 55 µNm at a voltage of 80 V by optimizing the preload between the stator and rotor. Moreover, a torque of approximately 100 µNm (10-g force generation by 1 mm radius) is obtained at higher voltages – this torque value is the largest in 2–3 mm scale motors reported to date. Two micro-flat ultrasonic motors drive a miniature two-link as direct-drive motors without gears. The motion of the two-link is demonstrated by an open-loop burst wave control, which is a pulse-width modulation control for an alternative voltage. Although the demonstration is simple, it shows the feasibility of the smallest and most practical link mechanism. GRAPHICAL ABSTRACT: